48 Assessment of bilateral limb differences in unipedal functional performance tests. (12th October 2015) - Madsen, LP; Hall, EA; Docherty, CL
Abstract : Background: Functional performance tests are often used in determining return to play criteria following an injury. However little research has been conducted to determine how limb dominance affects performance on many physical function tests. Objective: To determine differences between the dominant and non-dominant limbs during unipedal hopping tests. Design: Descriptive laboratory study. Setting: Research laboratory. Participants: Twenty-six physically active adults (16 females and 10 males) between 18 and 30 years of age with no history of ankle sprains or instability. Interventions: Six unipedal hopping tests were investigated: Side hop, triple crossover hop, 6-metre crossover hop, lateral hop for distance, medial hop for distance, and figure-8 hop. For each test, three trials were completed on each limb. Main outcome measurements: For side hop, 6-metre crossover hop, and figure-8 hop the fastest trial (sec) was used for statistical analysis. For the triple crossover hop, lateral hop for distance, and medial hop for distance the greatest distance (cm) was used for statistical analysis. Differences between the dominant and non-dominant limbs were compared for each test using a paired-samples t-test. Results: No dominant versus non-dominant limb difference was identified for the side hop (p = 0.63), 6-metre crossover hop (p = 0.70), lateral hop for distance (p = 0.18), medial hop for distance (p = 0.83), and figure-8 hop (p = 0.37) tests. There was a significant difference in scores for the triple crossover hop test (p = 0.01). Performance on the dominant limb (418.35 ± 100.40 cm) was significantly better than the non-dominant limb (405.12 ± 106.57 cm). Conclusions: Five of the six tests yielded no differences in performance between the dominant and non-dominant limbs. Therefore, from a rehabilitation perspective, healthcare providers can use these unipedal hopping tests to evaluate physical function following an injury without concern to whether the injury is sustained in the dominant or non-dominant side. The triple crossover hop test should be avoided since the dominant limb performed significantly better on this test.